2019
DOI: 10.3126/jie.v15i2.27640
|View full text |Cite
|
Sign up to set email alerts
|

Assessment on Corrosion Damage of Steel Reinforced Concrete Structures of Kathmandu Valley Using Corrosion Potential Mapping Method

Abstract: Present study is focused to investigate the corrosion damage conditions of steel reinforced twenty eight different types of the concrete structure samples from Kathmandu valley using a non-destructive technique of the corrosion potential mapping (CPM) method in accordance with ASTM C876-91 Standards. It is found from the present assessment that the building roof of public owners house, hume pipes and building pillars used in Kathmandu valley are generally under the low risk of reinforced steel corrosion in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Extensive research has led to the discovery of a new class of corrosion inhibitors that are eco-friendly. Previous studies were reported about the corrosion behavior of different ferrous structural materials used in Nepal in different corrosive environments [42][43][44][45][46][47][48][49][50][51], although a few studies were focused on the effects of eco-friendly plant-extracted green inhibitors on the mild steel corrosion [14,15,18]. In this context, the present work was aimed to study the effects of four inorganic compounds; Ca(NO 3 ) 2 , ZnSO 4 , (…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has led to the discovery of a new class of corrosion inhibitors that are eco-friendly. Previous studies were reported about the corrosion behavior of different ferrous structural materials used in Nepal in different corrosive environments [42][43][44][45][46][47][48][49][50][51], although a few studies were focused on the effects of eco-friendly plant-extracted green inhibitors on the mild steel corrosion [14,15,18]. In this context, the present work was aimed to study the effects of four inorganic compounds; Ca(NO 3 ) 2 , ZnSO 4 , (…”
Section: Introductionmentioning
confidence: 99%
“…The CoP of each steel bar was recorded on a digital multi‐meter (UNI‐T Business, Hong Kong) using a saturated calomel electrode (SCE) and exposed steel rod of the concrete slab as a reference and working electrodes, respectively, as described elsewhere. [ 44 ] Eight points, marked like pt‐1, pt‐2, pt‐3, pt‐4, pt‐5, pt‐6, pt‐7, and pt‐8 at equidistant from the sides, were marked on each SCR slab surface. The SCE and steel rod was connected, respectively, to the negative and positive terminals of the voltmeter for the CoP measurement of all eight points of each slab after 1 week to about 5 months.…”
Section: Methodsmentioning
confidence: 99%
“…[36] Besides, the XPS surface analysis confirmed the formation of iron oxy-hydroxy (FeOOH) species, which developed the hypothesis on the responsibility of iron-polyphenol insoluble organometallic compounds for anticorrosive properties. [37] However, to the best of the author's knowledge and belief, the anticorrosive behavior of the LEPG and its blend with LEMI to the SRC structures have not been virtually clarified yet, although few studies reported the corrosion conditions of different steel materials in concrete infrastructures, [39,40] and in soil environments [41][42][43][44] of Nepal. In this vein, current research explores a viable cement-based additive as an anticorrosive substance derived from the untapped leaf part of Nepal-origin M. indica and P. guajava plants to monitor the corrosion condition of steel bars embedded in the concrete slab.…”
Section: Introductionmentioning
confidence: 99%